Kepatuhan Minum Obat Berbasis Teori Model Imogene King pada Pasien Hipertensi - Sunaringtyas, Widyasih; Habibah, Diana Binti Tri (Universitas Muhammadiyah Klaten, 2023)
Hypertension is still an important problem for elderly. Most of those who suffer from hypertension are elderly, the aging process which has an impact on weakening brain function can cause mild memory problems or dementia so that most elderly people are disobedient to drinking, because they forget. The family as a companion to the elderly plays a role in reminding them through communication and function as a support system. The aim of this study was to determine adherence to taking hypertension medication based on the Imogene King model theory. The research design used is quantitative descriptive. The population in this study was 45 respondents, while the sample used was 40 respondents, using a purposive sampling technique in the UPTD Work Area of the Bendo Health Center, Pare District, Kediri Regency. Research variables on medication adherence based on Imogene King's model theory in hypertensive patients. This research instrument uses a questionnaire. Data analysis uses percentages and is interpreted quantitatively. The results of the research from 40 respondents, the majority of respondents, namely 28 (70%) were obedient to taking hypertension medication and a small portion of respondents, 12 (30%) were quite obedient in taking hypertension medication. The research results showed that the majority of respondents adhered to taking hypertension medication. It is hoped that the Imogene King model's theoretical interaction system can become a model for increasing medication adherence for families who have elderly family members who suffer from hypertension so that blood pressure is well controlled.